The Red Cross orphans - Peters, Glynis (London : One More Chapter, 2022)
Orphan Kitty Pattison is young and naive when she volunteers with the Red Cross. She meets fellow volunteers Joan Norfolk and Trixie Dunn, and a bond of friendship is forged during the Blitz. Days are spent nursing injured soldiers and caring for orphans just like herself. Nights are spent anticipating bombs falling from the sky and then trawling through the wreckage to save who she can, but the light and laughter she finds with Jo and Trix see Kitty through the darkest hours. And when Kitty starts growing closer to handsome Canadian doctor Michael McCarthy, it's her friends who help her find the courage to realize we all deserve love.
ardfic01/23.
jla01/23.
Keywords: Female friendship -- England -- 20th century -- Fiction; Man-woman relationships -- England -- 20th century -- Fiction; Orphans -- England -- 20th century -- Fiction; Red Cross and Red Crescent -- England -- Employees -- 20th century -- Fiction; Volunteer workers in medical care -- England -- 20th century -- Fiction; World War, 1939-1945 -- England -- Fiction; Historical fiction